To simplify the expression \((3p+6)(6p^2−8p−1)\), we will use the distributive property (also known as the FOIL method for binomials).
-
Distribute \(3p\) to each term in the second polynomial:
\[ 3p \cdot 6p^2 = 18p^3 \] \[ 3p \cdot (-8p) = -24p^2 \] \[ 3p \cdot (-1) = -3p \]
-
Distribute \(6\) to each term in the second polynomial:
\[ 6 \cdot 6p^2 = 36p^2 \] \[ 6 \cdot (-8p) = -48p \] \[ 6 \cdot (-1) = -6 \]
-
Combine all these results:
Now, we add all the results together:
\[ 18p^3 + (-24p^2 + 36p^2) + (-3p - 48p) - 6 \]
Combine like terms:
- For \(p^2\): \(-24p^2 + 36p^2 = 12p^2\)
- For \(p\): \(-3p - 48p = -51p\)
So we have:
\[ 18p^3 + 12p^2 - 51p - 6 \]
The simplified result of the expression \((3p+6)(6p^2−8p−1)\) is:
\[ \boxed{18p^3 + 12p^2 - 51p - 6} \]